Breast Reconstruction during the COVID-19 Pandemic: A Systematic Review. Issue 9 (22nd September 2021) - Hemal, Kshipra; Boyd, Carter J.; Bekisz, Jonathan M.; Salibian, Ara A.; Choi, Mihye; Karp, Nolan S.
Abstract : Introduction: The COVID-19 pandemic posed unique challenges for breast reconstruction. Many professional organizations initially placed restrictions on breast reconstruction, leading surgeons to conceive innovative protocols for offering breast reconstruction. This study reviewed the current evidence on breast reconstruction during the COVID-19 pandemic to provide guidance for surgeons facing future crises. Methods: The MEDLINE, EMBASE, and Cochrane Database of Systematic Reviews were searched for studies (1) describing implant and autologous breast reconstruction following mastectomy and (2) occurring during or pertaining to the COVID-19 pandemic. Results: Of the 1347 studies identified, 26 were included. Studies discussed type of reconstruction (18, 69%), complications (11, 42%), timing of reconstruction (10, 38%), protocols (10, 38%), COVID-19 screening (7, 27%), and length of hospital stay (7, 27%). The type of reconstruction varied depending on the stage of the pandemic: early on, autologous breast reconstruction was halted to preserve resources, but was later resumed. Within implant-based reconstruction, direct-to-implant was favored over serial tissue expansion. Several protocols were developed, with many emphasizing multidisciplinary collaborations for patient selection, use of specialized measures to reduce risk of COVID-19 transmission, and optimization of same-day discharge. Complication rates following breast reconstruction were similar to pre-pandemic rates. Conclusions: The COVID-19 pandemic has forever changed the landscape of breast reconstruction by raising important questions about delivery of care, cost, and resource utilization. The findings of this review may inform surgeons as they plan for similar future crises or strive for improved patient care and efficacy even during nonpandemic times.